Unique Temporal Expression of Triplicated Long-Wavelength Opsins in Developing Butterfly Eyes - Arikawa, Kentaro; Iwanaga, Tomoyuki; Wakakuwa, Motohiro; Kinoshita, Michiyo (Frontiers in Neural Circuits, 2017)
Following gene duplication events, the expression patterns of the resulting gene copies can often diverge both spatially and temporally. Here we report on gene duplicates that are expressed in distinct but overlapping patterns, and which exhibit temporally divergent expression. Butterflies have sophisticated color vision and spectrally complex eyes, typically with three types of heterogeneous ommatidia. The eyes of the butterfly Papilio xuthus express two green- and one red-absorbing visual pigment, which came about via gene duplication events, in addition to one ultraviolet- and one blue-absorbing visual pigment. We localized mRNAs encoding opsins of these visual pigments in developing eye disks throughout the pupal stage. The mRNAs of the ultraviolet and blue opsin are expressed early in pupal development, specifying the type of the ommatidium in which they appear. Red sensitive photoreceptors first express a green opsin mRNA, which is replaced later by the red opsin mRNA. Broadband photoreceptors (that coexpress the green and red opsins) first express the green opsin mRNA, later change to red opsin mRNA and finally re-express the green opsin mRNA in addition to the red mRNA. Such a unique temporal and spatial expression pattern of opsin mRNAs may reflect the evolution of visual pigments and provide clues toward understanding how the spectrally complex eyes of butterflies evolved.